EXTRACTION, CHARACTERIZATION AND EPOXIDATION OF CASTOR SEED OIL - Fredrick , F. Y.; Abdullahi, Abdullahi M.; Ibrahim , Muhammad Nazipi; Chiroma, Muhammad Bello; Girbo, Adamu A. (FUDMA JOURNAL OF SCIENCES, 2023)
Chemical epoxide modification appears to be one way toward the objective of substituting raw materials for industrial products, and epoxidized vegetable oils offer intriguing options as a raw material substitute for industrial chemicals.. The oil from castor seeds was extracted using a soxhlet extractor and the percentage yield for castor oil was 49 %. The characterization of castor oil yielded the following results: iodine value 88.52g I2/100g, acid value 1.148 mgKOH/g, saponification value 185.8 mgKOH/g, specific gravity 0. 9223 g, peroxide value 156.2 mEq/kg, and pH value 5.7. The oil was epoxidized in the presence of sulphuric acid using 30 % aqueous hydrogen peroxide as an oxygen donor and glacial acetic acid as an oxygen carrier. The fresh oil and the product of the epoxidation reaction were characterized using FTIR analysis, which revealed the disappearance of the carbon-carbon double bond peak at 1746.71 cm-1 and the formation of the epoxide peak at 1743.93 cm-1. Curing time analysis revealed the strength of the synthesized epoxide, with castor epoxide hardening at 25 min and commercial epoxide hardening at 8 min. Castor oil can be utilized as a raw ingredient in a variety of industrial applications, including water treatment, soap production, paint formulation, and laminate production.
Keywords: Curing time; functional group; industry; Acid Value; peroxide value; Iodine value